Reducing Plastic Waste in the Philippines : An Assessment of Policies and Regulations to Guide Country Dialogue and Facilitate Action - World Bank (Washington, DC, 2022)
Solid waste management (SWM) in the Philippines continues to be hampered by gaps and issues despite the passage of the Ecological Solid Waste Management Act of 2000. One of these issues involves plastic waste whose impacts have extended beyond the country’s terrestrial boundaries. Studies have shown that the Philippines, together with China, Indonesia, Thailand, and Vietnam, accounts for 55 to 60 percent of plastic waste entering the ocean. Globally, the Philippines has one of the highest rates of mismanaged plastic waste recycling, with only about 28 percent of the key resins it consumed in 2019 being recycled. Unrecycled plastics are disposed of in dumpsites and landfills, remain as litter, or accumulate in sewers, drainage systems, and rivers before being discharged into surrounding marine water bodies. This study assesses national-level policies governing the management of plastics waste in the Philippines. The study aims to support the government’s efforts to improve the management of such waste and to facilitate circular-economy practices. The study included a desk review and analysis of current SWM conditions, existing policies, and current and pending legislation related to recycling and plastics waste management. Consultations with key stakeholders in the private and public sectors in plastics waste management supplemented the review.